Environmental friendly vehicle - Jasni, Jasronita; Mailah, Nashiren Farzilah; Mariun, Norman (2002)
Pollution has become a topic that most talked about by public. This is due to the increasing deteriorating Condition of the environment namely the earth, water and air. In order to help in preserving the environment, vehicle manufacturers have decided to construct an environmental friendly vehicle. The combustion by-products of the burning in the engine are dangerous to human health especially to human respiratory system. It also interacts with the environment due to cause a chain reaction that further damaging the environment. This environmental friendly vehicle or better known as hybrid vehicle will help in reducing the effects of pollution by combining the internal combustion engine of a conventional vehicle with the battery and electric motor of an electric vehicle. It has the same advantages of the conventional vehicle with the environment benefits of the electric vehicle. In short, the benefits offered by the hybrid vehicle help in preserving the environment without compromising the efficiency of the most favoured personal transportation vehicle.